PERIODONTAL TISSUE HEALTH TRAINING FOR PREGNANT WOMEN AND CADRES AT PASURUAN PRIMARY HEALTH CENTERS TO AVERT STUNTING - I Komang Evan Wijaksana; Irma Josefina Savitri; Eka Fitria Augustina; Agung Krismariono (Universitas Airlangga, 2023)
In Indonesia, stunting continues to be a problem for public health, even in Pasuruan City. In Pasuruan City, 1,516 kids still run the risk of developing stunting. The Pasuruan City Government works to keep the rate of stunting under 14%. To reduce the likelihood that children with stunting will be born, pregnant mothers are the main focus of prevention efforts. Inflammatory diseases in the mouth can set off pregnancy complications that have the potential to result in preterm birth, low birth weight babies (LBW), and eventually become the cause of stunting in children. This community service is carried out in the form of training and counseling on periodontal tissue and oral health for pregnant women and health cadres at the Pasuruan City Health Center to increase knowledge of stunting prevention in Pasuruan City. Community service was carried out at four health centers in Pasuruan City, namely the Kandangsapi, Bugul Kidul, Kebonsari, and Trajeng Health Centers. The target partners in community service are health cadres and pregnant women in the work area of ​​each health center. The form of service carried out is counseling and training. Education initiatives were conducted on the subject of periodontal tissue health, its relationship to pregnancy, the prevalence of LBW, and the possibility of stunting effects on the periodontal tissue health of pregnant women. The cognitive and psychomotor health of cadres and pregnant women can be improved by community service in the form of counseling and training.